The dyscalculia assessment - Emerson, Jane.; Babtie, Patricia (b, 2013)
This work contains the information you will need to pinpoint a child's difficulties with numeracy and uses that information to show you how to help the child progress
Includes bibliographical references and index.
Keywords: Mathematics -- Study and teaching; Dyslexic children -- Education; Learning disabilities -- Education